2010
DOI: 10.1038/nrneph.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, diagnosis and management of paraneoplastic glomerulonephritis

Abstract: Paraneoplastic glomerulonephritis is a rare complication of malignancy that is frequently mistaken for idiopathic glomerulonephritis. Failure to recognize paraneoplastic glomerulonephritis can subject patients to ineffective and potentially harmful therapy. Pathology of paraneoplastic glomerulonephritis varies between different types of malignancies. This Review describes the association of glomerulonephritis with both solid tumors and hematological malignancies The pathogenetic mechanisms of many glomerular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
165
3
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(193 citation statements)
references
References 111 publications
3
165
3
15
Order By: Relevance
“…As for IgA deposits in the present case, it could not be clarified if its cause is a drug, is associated with mucosal immunity of lung cancer, or complication of IgA nephropathy. Although rare, both solid tumor such as renal cell cancer, lung cancer, pancreas cancer, and hematological malignancies such as Hodgkin's and non-Hodgkin's diseases, could induce IgA nephropathy, termed paraneoplastic IgA nephropathy [15,16]. Interestingly, a case is recently reported that IgA nephropathy occurs in gefitinib treatment for lung cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…As for IgA deposits in the present case, it could not be clarified if its cause is a drug, is associated with mucosal immunity of lung cancer, or complication of IgA nephropathy. Although rare, both solid tumor such as renal cell cancer, lung cancer, pancreas cancer, and hematological malignancies such as Hodgkin's and non-Hodgkin's diseases, could induce IgA nephropathy, termed paraneoplastic IgA nephropathy [15,16]. Interestingly, a case is recently reported that IgA nephropathy occurs in gefitinib treatment for lung cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…La NM generalmente se asocia a carcinomas sólidos y la NCM a procesos linfoproliferativos [10][11][12] . Se han descrito con menor frecuencia glomerulonefritis (GN) por IgA, GN mesangiocapilar, gloméruloesclerosis focal y segmentaria, GN crecéntica, amiloidosis y microangiopatía trombótica 12,13 .…”
Section: Discussionunclassified
“…Con menor frecuencia: renales, prostáticos, colorrectales, mamarios, pancreáticos, tímicos, etc 12,13 . Es extremadamente raro que un SN se asocie a tumores ginecológicos 1,11,12,14 .…”
Section: Discussionunclassified
See 2 more Smart Citations